Non‐uniform displacement and strain between the soleus and gastrocnemius subtendons of rat Achilles tendon. (23rd November 2017) - Finni, T.; Bernabei, M.; Baan, G. C.; Noort, W.; Tijs, C.; Maas, H.
Abstract : Achilles tendon (AT) comprises of 3 subtendons arising from the soleus (SOL) and the lateral (LG) and medial (MG) heads of the gastrocnemius muscle. While recent human studies show differential displacement within AT, these displacements have not been attributed to specific subtendons. We tested the hypothesis that the SOL and LG subtendons show differential displacement and strain during various combinations of SOL, LG, and MG excitations. Movement of knots, sutured onto SOL and LG subtendons of 12 Wistar rats, was videotaped, while the muscles were stimulated intramuscularly and ankle torque was assessed. When SOL only was stimulated, the plantar flexion torque was the smallest among the different conditions ( P  < .001). In this condition, from passive to active state, the displacement (0.57 vs 0.47 mm, P  = .002) and strain (8.4% vs 2.4%, P  < .001) in the SOL subtendon were greater than in LG subtendon. When LG only was stimulated, a higher ankle torque was measured as compared to SOL stimulation ( P  < .001); the displacement was similar in both subtendons (~0.6 mm), while the strain was greater in LG than in SOL (4.7% vs 1.7%, P  < .001). When all 3 muscles were stimulated simultaneously, ankle torque was highest and the displacement (0.79 vs 0.74 mm, P  = .002) and strain (7.7% vs 4.4%, P  = .003) were greater in SOL than in LG. These data show that the different subtendons of AT can experience relative displacement and differential strains. Together with anatomical dissections, the results revealed that such uniformities may be due to a lower stiffness of SOL subtendon compared to LG.